Effective communication in an emerging CCS industry – an application of the SPE SRMS to convey contingencies, uncertainties, commerciality, and progress to project approval - Chernik, Paul S.; Caniggia, Matteo; Mitchell, Ellen (Frontiers in Energy Research, 2024)
At COP28, Carbon Capture, Utilization, and Storage was declared a removal technology whose application must be accelerated. In 2017, the Society of Petroleum Engineers (SPE) published the CO2 Storage Resource Management System (SRMS) as a framework for stakeholder communication. The SRMS guidelines were designed to support the creation of reports that inform readers regarding the contingencies that must be overcome to obtain project approval, uncertainty in the mass of CO2 that can be stored, and the commerciality of the project. However, working examples where the SRMS has been used to communicate project status in the public domain are limited. In 2023, the authors of this paper referred to the SRMS as the standard for completing an expert report, termed a Competent Persons Report (CPR), for the Viking Carbon Capture and Storage (CCS) development in the United Kingdom. During the application of the SRMS framework, challenges were identified in conveying the progress made by the project proponent in identifying and addressing technical risks. This paper describes innovations developed to supplement the SRMS guidelines and improve communication with stakeholders. First, a flowchart was developed to explain a vital interpretation of the SRMS. Next, a defined framework of technical milestones was designed to assess the maturity of a given technical topic within the SRMS. This framework was combined with radial data visualization. The combination allowed multiple storage sites to be compared simultaneously and allowed stakeholders to quickly identify the maturity of technical analysis for any given site. We conclude that improving the consistency and clarity of CCS reporting to stakeholders can help build trust in this emerging industry.